Microbiological evaluation on raw materials and food contact surfaces of ‘keropok lekor’ premises in Kuala Nerus, Terengganu and their prevalence of antibiotic resistant bacteria - Mohd Nizam Lani; Tan, Ai Peng; Zarizal Suhaili; Zaiton Hassan (Penerbit Universiti Kebangsaan Malaysia, 2017)
‘Keropok lekor’ is a popular street food and widely available in Terengganu. However, there is limited study on the microbiological status of sources of contamination from ‘keropok lekor’ premises in Terengganu. Microbiological quality of raw materials and food contact surfaces were determined by Total Plate Count, coliform count, Staphylococcus spp. and Vibrio spp. count. The presumptive of Escherichia coli, Staphylococcus aureus and Vibrio spp. were further identified by phenotypic identification such as IMViC tests and API20 NE identification system. The antibiotic resistance of the identified bacteria was determined using disc diffusion method. Escherichia coli and Vibrio were predominant microorganisms isolated from raw materials, whereas Staphylococcus was the predominant microorganism on food contact surfaces. The boiling process of ‘keropok lekor’ at 100°C was significantly (p < 0.05) reduced the Total Plate Counts, coliform, Staphylococcus spp. and Vibrio spp. count for safe consumption. The identified antibiotic resistance of E. coli, S. aureus and Vibrio spp. showed that the bacteria were within controllable emergence strains, whereby the present antibiotics used are able to suppress the growth. Regular monitoring programme is essential to further improve the microbiological quality of raw materials and food contact surfaces.